Illegal Animal Trade by Crime Groups between Indonesia and Australia Becomes a Phenomenon that Threatens Global Issues - Putri, Ayu Anggraini (Universitas Djuanda, 2024)
This research explains the phenomenon of illegal animal trade, which is one of the organized transnational crimes in the current era of globalization. Australia and Indonesia are countries affected by the illegal animal trade, making it a global threat that cannot be overcome easily. The research question is why illegal animal trade between Australia and Indonesia has become a strong network at the international level and threatens a global issue. The aim of this research is to analyze one case of TOC, namely the illegal animal trade that occurred between Indonesia and Australia, because this issue is a phenomenon that threatens global issues and has become a strong network at the international level. Data was collected through various literature sources and literature studies, and document review techniques were used for the data collected in this research. Data analysis uses analysis with a descriptive and qualitative approach. The amount of literature used in this research was 12 journal articles, 8 newspapers and reports, five repositories, two theses, and three books. The results of the analysis found several findings and answers from this research, namely that this phenomenon involves two countries, apart from that this crime causes other crimes, and the perpetrators are part of an organized crime group that has many networks at the international level to carry out illegal animal trade on the international black market.